DEVELOPMENT OF EDMODO-BASED E-LEARNING MEDIA OF GEOGRAPHY LESSON CLASS XI STATE SENIOR HIGH SCHOOL 1 OF SUWAWA - Nur'ain Hamzah; Sri Maryati; Syahrizal Koem (GeoEco, 2023)
The Covid-19 pandemic brought challenges for education sector in the learning process. The problems faced in learning during the pandemic were the lack of use of ICT-based media by teachers. This study aims to produce Edmodo-based learning media of geography lesson on the topic of Indonesian cultural diversity. This development research applied ADDIE model that consist of five stages includes analysis stage, design stage, development stage, implementation stage, and the evaluation stage. The results of the media development were validated by three experts namely media design expert, material expert, and geography teacher. The validation result from media design expert is very valid with score of 87.27%. Validation result from material expert is very valid with scored 80%, and validation from geography teacher is very valid with score of 88%. Media trials were carried out on students to collect student responses on the clarity of the material, appearance of the media, ease of understanding, and the use of language. The average student response to learning media gets 91.82%. Based on the research result, it can be concluded that the Edmodo-based learning media is suitable for learning process both offline and online learning.